RETROSPECTIVA ISTORICA SI CONCEPTELE ACTUALE IN ETIOPATOGENIA SI CLASIFICAREA BOLILOR PARODONTALE. DATE DIN LITERATURA - Silvia Martu (Romanian Journal of Medical and Dental Education, 2016)
Periodontal diseases are arguably among the most ancient and common infectious diseases affecting humans, leading to permanent destruction of the supporting structures of the dentition and ultimately tooth loss. It has been established that dental biofilm, consisting of many microbial species and their products, is an etiological agent of periodontal disease. It is widely accepted that immunological and inflammatory responses to dental plaque via hostparasite interaction are manifested by clinical signs and symptoms of periodontal diseases. The outcome of this interaction can be modulated by other components known as risk factors (modifiers), either inherent (genetic) or acquired (environmental) in nature, significantly affecting the initiation and progression of periodontal diseases of different types. While definitive genetic factors responsible for either susceptibility or resistance to periodontal diseases await definitive identification and verification. Currently, periodontal diseases are classified based upon clinically observed disease traits using radiographs and clinical examination: gingivitis; chronic periodontitis; aggressive periodontitis; periodontitis as manifestation of systemic diseases; necrotizing ulcerative periodontitis; abscesses of the periodontium; periodontitis associated with endodontic lesions; and developmental or acquired deformities and conditions. Advances in genomics, molecular science, and personalized medicine may result in guidelines for unambiguous disease definition and diagnosis in the future.